Secondary metabolites isolated from Agrimonia pilosa Ledeb. Issue 1 (22nd December 2021) - Li, Hong-Rui; Li, Yu-Kui; Xiao, Jian; Yang, Cui; Jiang, Meng-Yuan; Tian, Kai; Wang, Wei; Li, Yan-Hong; Huang, Xiang-Zhong
Abstract: A pilot study on the ethanol extracts of Agrimonia pilosa found to have anti- α -glucosidase and anti-inflammatory activities. Subsequent chemical study afforded a new phenylethyl isocoumarin glycoside (1 ) and eight known compounds (2-9 ). The structure of 1 was elucidated by comprehensive spectroscopic analysis and chemical transformations. All compounds showed modest α-glucosidase inhibitory activity (IC50 values ranging from 36.8 to 210.7 μM), which was lower than that of the positive control acarbose (IC50 =301.9 μM). Those compounds except inactive compounds 3 and 6 showed weak anti-inflammatory activity.